Anaemia of Plasmodium falciparum malaria. - Phillips, R; Pasvol, G (1992)
The pathophysiology of the anaemia of falciparum malaria is both complex and multifactorial, and results in a condition which is a major cause of mortality and morbidity in patients, especially children and pregnant women, living in malarial endemic areas. The importance of anaemia as a cause of death in malaria may well be underestimated because of difficulty in diagnosis, especially where parasitaemia may be low and the clinical picture may be confused with other causes of anaemia. Two clinical presentations predominate: severe acute malaria in which anaemia supervenes, and severe anaemia in patients in whom there have been repeated attacks of malaria. The major mechanisms are those of red cell destruction and decreased red cell production. Potential causes of haemolysis include loss of infected cells by rupture or phagocytosis, removal of uninfected cells due to antibody sensitization or other physicochemical membrane changes, and increased reticuloendothelial activity, particularly in organs such as the spleen. Decreased production results from marrow hypoplasia seen in acute infections, and dyserythropoiesis, a morphological appearance, which in functional terms results in ineffective erythropoiesis. The role of parvovirus B19 as a possible cause of bone marrow aplasia in a few cases is postulated. Finally, there is now evidence which points to genetic factors, HLA associated, which may protect against the development of malarial anaemia and which has become common in areas endemic for malaria.